Aviation : an historical survey from its origins to the end of the Second World War - Gibbs-Smith, Charles Harvard, 1909-1981. (London : Science Museum, 2003)
In this classic account, Charles Gibbs-Smith traces the story of aviation from the invention of the kite in China through to the beginnings of the jet age. In particular, the book gives a lovingly-reconstructed account of the experiments, disasters and successes in many countries which culminated in the achievement of a genuine flying machine by the Wright brothers in the United States. A large part of Gibbs-Smith's story also covers the early years of aviation before 1914. This period, rich in eccentric characters and extraordinary efforts, laid the foundation for future progress. The second edition of Gibbs-Smith's authoritative text, out of print for many years, is here republished with a number of new illustrations. It will delight a new generation of aviation enthusiasts. Book jacket.
Dreams, myths and devices -- From classical antiquity to the end of the sixteenth century -- The seventeenth century -- The eighteenth century -- Cayley, and the first half of the nineteenth century -- The 1850s and 1860s -- The 1870s -- The 1880s -- The powered prelude to practical flying: 1890-1903 -- The gliding prelude to practical powered flying -- The Wright brothers and the invention of the practical aeroplane: 1899-1905 -- The beginnings of practical aviation in Europe: 1902-08 -- The aeroplane as an accepted vehicle: 1909 -- Practical powered flying: 1910-14 -- The First World War: 1914-18 -- Between the wars: the first period: 1919-29 -- Between the wars: the second period: 1930-39 -- The Second World War: 1939-45.
Previous edition: London: HMSO, 1985.
"This 2003 edition omits the quotations on flying, bibliography and conversion tables featured in the 1985 edition"-Page 6.
Includes bibliographical references and index.
Keywords: Aeronautics -- History; Airplanes -- History; Aeronautics; Airplanes; History